Introducing an interactive story in a geolocalized experience - López-Arcos, José R; Gutiérrez Vela, Francisco L; Padilla-Zea, Natalia; Paderewski-Rodríguez, Patricia; Medina Medina, Nuria (ACM International Conference Proceeding Series, Interaccion 2017, 2020)
Pervasive games are one of the types of gaming experiences that currently causes the most impact on players. They break the usual environment of the game in a spatial, temporal or social dimension. The integration of the narrative with the interactivity and the geolocalization of these games requires a model that represents and structures the story and its integration with the rest of the elements of the game. In addition, this model should allow us to analyze the effectiveness of the story and how it helps to create a good user experience. In this paper, we propose a strong structuring of the narrative that includes geolocalization support. Through an example of the design of an interactive geolocalized story, we explain several characteristics of the model that make possible the creation of a good interactive narrative.
Conferencia de "18th International Conference on Human Computer Interaction, Interaccion 2017; Cancun; Mexico; 25 September 2017 through 27 September 2017"
Keywords: geolocalized narrative; pervasive games; storytelling; user experience; videogames; Scopus(2)